The effect of camel milk curd masses on rats blood serum biochemical parameters - Dikhanbayeva, F.; Zhaxybayeva, E.; Smailova, Z .; Issimov, A.; Dimitrov, Z .Z .; Kapysheva, U.; Bansal, N. (PLOS ONE. - 2021., 2021)
This study aimed to assess potential feeding effect of camel milk curd mass and its mixes to experimental rat's blood serum biochemical parameters, enzymatic activity and the peptide toxicity. Fifty healthy male Sprague-Dawley rats were divided into five groups (n = 10 each). Each group was fed with camel milk pure curd mass and its mixes for 16 days. At the end of the experiment, rats were sacrificed to collect the samples from the blood serum. Blood serum biochemical parameters total protein, cholesterol, glucose, albumin, triglycerides; the enzymatic activities of alanine aminotransferase, aspartate aminotransferase, alkaline phosphatase were determined on the A25 automatic analyser, and peptide toxicity analysed by the reference method. The statistical data have shown no significant differences in body weight gain in all groups. Total protein decreased in group II, IV, and V; however, it increased in group III compared to the control group. Cholesterol grew up in group II and it slightly increased in group V, dropped in groups III and IV compared to group I result. Glucose increased in groups II, III, IV compared to group I; still, group V results show a slight decrease. Albumin decreased in group IV, yet in group V it increased than the group I result. Simultaneously, groups II and III results were changed with less percentage. Triglyceride grew up in groups II, V, and it dropped significantly in groups III, IV compared to the control group. De Ritis ratio of enzymes in groups II, III, and IV fluctuated between 1.31 and 0.98 IU/L; however, group V demonstrated significant data versus group I. Diets peptide toxicity in all groups was lower than control group data. The experimental results indicated that curd mass from camel milk could be used as a pure or with additives and it did not discover the observed side effects. Это исследование было направлено на оценку потенциального эффекта кормления творожной массой верблюжьего молока и его смесей на биохимические параметры экспериментальной сыворотки крови крыс, ферментативную активность и токсичность пептидов. Пятьдесят здоровых самцов крыс Sprague-Dawley были разделены на пять групп (n = 10 в каждой). Каждую группу кормили чистой творожной массой из верблюжьего молока и ее смесями в течение 16 дней. В конце эксперимента крыс умерщвляли для сбора образцов сыворотки крови. Биохимические показатели сыворотки крови: общий белок, холестерин, глюкоза, альбумин, триглицериды; ферментативную активность аланинаминотрансферазы, аспартатаминотрансферазы, щелочной фосфатазы определяли на автоматическом анализаторе А25, а токсичность пептидов анализировали эталонным методом. Статистические данные не показали достоверных различий в приросте массы тела во всех группах. Общий белок снизился во II, IV и V группах; однако он увеличился в группе III по сравнению с контрольной группой. Холестерин увеличился во II группе и несколько увеличился в группе V, снизился в группах III и IV по сравнению с результатом I группы. Уровень глюкозы повышен во II, III, IV группах по сравнению с I группой; тем не менее, результаты группы V показывают небольшое снижение. Альбумин снизился в группе IV, но в группе V он повысился, чем результат группы I. При этом результаты II и III групп изменились с меньшей процентной долей. Триглицерид вырос во II, V группах и значительно снизился в группах III, IV по сравнению с контрольной группой. Коэффициент де Ритиса ферментов в группах II, III и IV колебался от 1,31 до 0,98 МЕ / л; однако группа V продемонстрировала достоверные данные по сравнению с группой I. Токсичность пищевых пептидов во всех группах была ниже, чем данные контрольной группы. Результаты экспериментов показали, что творожную массу из верблюжьего молока можно использовать в чистом виде или с добавками, и не было обнаружено наблюдаемых побочных эффектов.
Keywords: импакт-фактор 2021; скопус; web of science; кларивате аналитикс; творожная масса; верблюжье молоко; научный журнал; дальнее зарубежье; периодическое издание; сыворотка крови; состав крови